1996
DOI: 10.3382/ps.0751198
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Selection for Body Weight in Japanese Quail Under Different Environments

Abstract: Long-term selection was conducted for high 4-wk BW in Japanese quail under different selection environments to investigate selection limits and to determine whether genetic parameters for growth are similar to those in chickens. Quail lines were selected under an adequate 28% CP diet (P line) and under a low 20% CP diet (T line). Mean realized heritabilities ranged from 0.32 (T line) to 0.49 (P line) during the first 10 generations. Although genetic variation remained following 97 generations of selection, rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 21 publications
4
43
0
Order By: Relevance
“…Generally, the direct heritability estimates of live weights for males were higher than those of females. The heritability estimates in this study were similar to those reported by Michalska (1994), Marks (1996) and Schüler et al (1998), but were higher than those reported by Aggrey & Cheng (1994) and Saatci et al (2003). The heritability of the ASM was moderate and similar for males and females.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Generally, the direct heritability estimates of live weights for males were higher than those of females. The heritability estimates in this study were similar to those reported by Michalska (1994), Marks (1996) and Schüler et al (1998), but were higher than those reported by Aggrey & Cheng (1994) and Saatci et al (2003). The heritability of the ASM was moderate and similar for males and females.…”
Section: Resultssupporting
confidence: 79%
“…Knowledge of the heritability of traits is essential for understanding how individual characteristics change from one generation to another in response to selection (Falconer & Mackay, 1996). Studies of heritability have mostly focused on the estimation of genetic parameters for growth especially under different selection environments (Anthony et al, 1996;Marks, 1996;Saatci et al, 2003). However, selection rarely operates on only one characteristic at a time (Lande & Arnold, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The body weight differences between groups of generations were highly significant, except the parental generations (P<0.01). Previous selection studies also supported that the body weight of the populations significantly increased from the first generation (Marks, 1996;Oguz and Turkmut, 1999;Yolcu, 2005). The second generation female body weights for all groups were higher than male body weights.…”
Section: Resultsmentioning
confidence: 74%
“…Additionally, quails can be utilized for meat production within a month and mature at an early age of 6 weeks, such that female birds generally reach whole yield by approximately two months (Jatoi et al, 2013). The studies on Japanese quails generally focus on improvement of egg production in the early periods or the body weight of fixed age quails during short-and long-term selection programs (Marks, 1996;Yolcu, 2005;Minville, 2004;Narinc and Aksoy, 2012). To date, many selection studies have been performed in the fourth or fifth weeks of quails' body weight (Nestor et al, 1983;Marks, 1991;Antony et al, 1996;Oguz and Turkmut, 1999;Steigner et al, 1992;Khaldari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-four young adult birds (2 mo) and 24 aged birds (24 mo) were examined in the present study. The lifespan of Japanese quails is ϳ26 -28 mo, and they are both physically and sexually mature by 1.5 mo of age (25,28). The PAT muscle is flexed with the wing on the birds back at rest, but it is stretched when the wing is extended.…”
Section: Allmentioning
confidence: 99%